The Entrepreneur’s Psychological Capital, Creative Innovation Behavior, and Enterprise Performance - Gao, Qianying; Wu, Cisheng; Wang, Linchuan; Zhao, Xuyang (Frontiers in Psychology, 2020)
In order to analyze the relationship between entrepreneur psychological capital, creative innovation behavior, and enterprise performance based on the actual situation of Chinese enterprises, and provide a theoretical basis for the application of entrepreneur psychological capital in enterprise innovation and performance development, in this study, 536 entrepreneurs from 517 enterprises in different fields in Anhui region were selected, and a questionnaire survey on the psychological capital of entrepreneurs, creative innovation behaviors, and corporate performance was conducted. A hypothesis model of the relationship between entrepreneur’s psychological capital, creative innovation behavior, and enterprise performance was constructed. The correlation between entrepreneur’s psychological capital, creative innovation behavior, and enterprise performance and the intermediation of creative innovation behavior were analyzed using multiple regression model and structural equation model. The results show that there is a significant positive correlation between dimensions of self-efficacy (regression coefficient=0.682, p=0.000), toughness (regression coefficient =0.526, p=0.000), and enterprise performance; there is a significant positive correlation between the dimensions of optimism (regression coefficient =0.471, p=0.003), hope (regression coefficient =0.590, p=0.006), and enterprise performance; there is a significant positive correlation between entrepreneurs’ technological innovation behavior (regression coefficient =0.506, p=0.000), business innovation behavior(regression coefficient =0.562, p=0.000), and enterprise performance; there is a significant positive correlation between entrepreneurial relationship acquisition behavior (regression coefficient =0.632, p=0.004) and enterprise performance. Taking entrepreneurs’ creative innovation behavior as the intermediary variable, the authors conclude that the dimensions of entrepreneurs’ self-efficacy, hope, optimism, toughness, and the standardized path coefficient of enterprise performance are significantly reduced; through the analysis of structural equation model, it is found that the fitting index of the model of entrepreneur’s psychological capital, creative innovation behavior, and enterprise performance meets the fitting standard, which shows that both the psychological capital and the creative innovation behavior of entrepreneurs can promote the improvement of enterprise performance. Entrepreneur’s creative innovation behavior plays an intermediary effect in the positive influence of entrepreneur’s psychological capital on enterprise performance.